1989
DOI: 10.1007/bf01954855
|View full text |Cite
|
Sign up to set email alerts
|

Single injections of triazolam, a short-acting benzodiazepine, lengthen the period of the circadian activity rhythm in golden hamsters

Abstract: Single injections of the benzodiazepine, triazolam, induce phase shifts and cause a lengthening of the circadian activity rhythm in the golden hamster. The effect of triazolam on period depends on the phase of injection, but is not dependent on the direction of the phase shifts. Triazolam injections caused increases in period that were associated with phase advances as well as phase delays in the activity rhythm. This relationship between triazolam-induced phase shifts and changes in period is different from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Long-term alterations in free-running period following acute stimulation have been reported previously for photic (Pittendrigh and Daan, 1976), pharmacological (Joy et al, 1989;Edgar et al, 1993;Meyer et al, 1993), and arousal-related stimuli (Mrosovsky, 1993). In the present study, we noted a tendency for phase delays to be associated with period lengthening and for phase advances to be associated with period shortening, for both clonidine and saline treatments.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Long-term alterations in free-running period following acute stimulation have been reported previously for photic (Pittendrigh and Daan, 1976), pharmacological (Joy et al, 1989;Edgar et al, 1993;Meyer et al, 1993), and arousal-related stimuli (Mrosovsky, 1993). In the present study, we noted a tendency for phase delays to be associated with period lengthening and for phase advances to be associated with period shortening, for both clonidine and saline treatments.…”
Section: Discussionsupporting
confidence: 55%
“…A similar relationship between phase shift and period change has been noted previously in studies of photic phase shifting (Pittendrigh and Daan, 1976), but the results for non-photic phase shifting are inconsistent. For example, both triazolam and induced activity are associated with period lengthening (Joy et al, 1989;Mrosovsky, 1993), while serotonergic agonists are associated with period shortening . These effects are not systematically related to phase shift magnitude or direction, but were related to circadian time, showing "period-response" curves quite different from the corresponding PRCs.…”
Section: Discussionmentioning
confidence: 98%
“…Locomotor activity has previously been shown to influence the circadian period in nocturnal rodent species (Edgar et al, 1991a;Joy et al, 1989;Mrosovsky, 1993;Weisgerber et al, 1997;Yamada et al, 1988). The extent to which period changes reflect daily nonphotic phase shifts or direct effects on the period of the endogenous circadian pacemaker is not always clear.…”
Section: Discussionmentioning
confidence: 98%
“…Animal studies have shown that increased levels of physical activity are associated with changes in the period (Aschoff et al, 1973;Edgar et al, 1991;Gnaedinger and Rosenberg, 1992;Honma et al, 1991;Joy et al, 1989;Mrosovsky, 1993), phase (Janik and Mrosovsky, 1993;Joy et al,1989;Mrosovsky, 1991;Mrosovsky and Biello, 1994;Turek et al, 1995;Van Reeth et al, 1992), and entrainment (Mrosovsky and Salmon, 1987;Reebs and Mrosovsky, 1989;Turek et al, 1995;Van Reeth et al, 1993) of circadian rhythms. In humans, a large number of studies suggests that increased physical fitness improves both daytime performance and nighttime sleep, but its effect on circadian rhythms has received very little attention (Van Someren et al, 1994).…”
Section: Introductionmentioning
confidence: 97%